Hip-Hop Revolution in the Flesh - Thomas, G. author. aut Link
XII, 231 p. 13 illus.
Keywords: An extended study of the writings of Lil' Kim, the multi-platinum selling Hip Hop artist. Examines Lil' Kim's anti-sexist, gender-defiant and ultra-erotic verse alongside issues of race and the politics of imprisonment. This is the first study to apply the tools of literary criticism to Hip Hop's lyrical writings.